Rapid Seismic Vulnerability Assessment of Low- to Mid-Rise Reinforced Concrete Buildings Using Bingol's Regional Data - Ozhendekci, Nuri; Ozhendekci, Devrim (EARTHQUAKE ENGINEERING RESEARCH INST, 2012)
A methodology based on multiple linear regression analysis is used for rapid vulnerability assessment of a building set surveyed in the disaster area of the 1 May 2003 Bingol, Turkey, earthquake. The data set represents the population of low- to mid-rise reinforced concrete buildings in Bingol. In addition to the relevant statistical procedures for parameter selection, all possible regressions of selected building parameters are carried out, and the most appropriate regression function is determined. Structural system type, newly introduced span index, priority index, existence of captive columns, and soft story index are found to play the dominant role. A leave-one-out cross validation method is utilized to test the reliability of derived regression function. The data collected during 1999 Duzce earthquake is also used for testing. The correct classification rate for both calibration and test data is found to be near 90%, despite an acceptable increase in incorrect classification rate. [DOI: 10.1193/1.4000065]
Keywords: SCREENING-PROCEDURE; SCHOOL BUILDINGS; TURKEY; PERFORMANCE; Engineering